Outcomes of water deficit stress on the physiological quality of soybean seeds - Grahl,Tiago Darlan (2022)
Abstract: This study aimed to compare the physiological seed quality of soybean cultivars produced under or without water deficit stress. Seed samples of three soybean cultivars produced in the 2019/2020 crop season were collected in a rural property and in a company that obtains the cultivars. In the rural property, the seeds were produced under water deficit stress and high temperatures during the crop’s and were characterized by the presence of greenish seeds. In the company that obtains the cultivars, the sample consisted of a certified seed lot produced under normal rainfall and temperature conditions, without greenish seeds. Germination, average germination time, germination speed index, average germination speed, the number of normal and abnormal seedlings, the seedling height and dry weight, the root evaluations (length, surface area, volume, average diameter and dry mass) and the total seedling dry mass were also evaluated. Soybean seeds produced under water deficit stress showed a reduction in physiological quality directly proportional to the percentage of greenish seeds present in each seed lot. The occurrence of water deficit stress on the soybean in the reproductive and maturation stages negatively impacts the soybean crop installation in the subsequent season due to the low physiological seed quality.